Red dawn [videorecording (DVD)] - Bradley, Dan; Hutcherson, Josh; Peck, Josh, 1986-; Hemsworth, Chris; Lucas, Isabel, 1985-; Palicki, Adrianne, 1983- (20th Century Fox Home Entertainment, 2013)
The unsuspecting citizens of Spokane, Washington, wake up one morning to the shocking sight of foreign paratroopers dropping from the sky in a surprise attack on the United States. Soon the entire city is under enemy control, but a group of courageous teenagers has decided to fight back, waging an all-out war against the invaders, to take back their town and their freedom!